What Does the Evidence Tell Us about ‘Thinking and Working Politically ’ in Development Assistance? - Dasandi, Niheer; Laws, Ed; Marquette, Heather; Robinson, Mark (Politics and Governance, 2019)
Abstract: This paper critically reviews evidence on ‘thinking and work ing politically’ in development. Scholars and practitioners have incre asingly recognised that development is fundamentally political, and ef forts are underway to develop more politically informed ways of thinki ng and working. The literature does not yet constitute a strong eviden ce base to link these efforts to more effective aid programming: much evidence is anecdotal, does not meet high standards of robustness, is not comparative, and draws on self-selected successes reported by prog ramme insiders. We discuss factors commonly considered to explain the success of politically informed programmes in areas where conventional programming approaches fall short. We consider evidence in three area s—political context, sector and organization—and provide guidance on w here to focus next. Finally, we outline ways of testing the core assum ptions of the ‘thinking and working politically’ agenda more thoroughl y, to provide a clearer sense of the contribution it can make to aid e ffectiveness.